Rowing performance, body composition, and bone mineral density outcomes in college-level rowers after a season of concurrent training - Young, K. C.; Kendall, K. L.; Patterson, K. M.; Pandya, P. D.; Fairman, P. C.; Smith, S. W. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To assess changes in body composition, lumbar-spine bone mineral density (BMD), and rowing performance in college-level rowers over a competition season. Methods: Eleven Division I college rowers (mean ± SD 21.4 ± 3.7 y) completed 6 testing sessions throughout the course of their competition season. Testing included measurements of fat mass, bone-free lean mass (BFLM), body fat (%BF), lumbar-spine BMD, and 2000-m time-trial performance. After preseason testing, rowers participated in a periodized training program, with the addition of resistance training to the traditional aerobic-training program. Results: Significant (P < .05) improvements in %BF, total mass, and BFLM were observed at midseason and postseason compared with preseason. Neither lumbar-spine BMD nor BMC significantly changed over the competitive season (P > .05). Finally, rowing performance (as measured by 2000-m time and average watts achieved) significantly improved at midseason and postseason compared with preseason. Conclusion: Our results highlight the efficacy of a seasonal concurrent training program serving to improve body composition and rowing performance, as measured by 2000-m times and average watts, among college-level rowers. Our findings offer practical applications for coaches and athletes looking to design a concurrent strength and aerobic training program to improve rowing performance across a season.